If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9v + 10 = v + 9 Reorder the terms: 10 + 9v = v + 9 Reorder the terms: 10 + 9v = 9 + v Solving 10 + 9v = 9 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 10 + 9v + -1v = 9 + v + -1v Combine like terms: 9v + -1v = 8v 10 + 8v = 9 + v + -1v Combine like terms: v + -1v = 0 10 + 8v = 9 + 0 10 + 8v = 9 Add '-10' to each side of the equation. 10 + -10 + 8v = 9 + -10 Combine like terms: 10 + -10 = 0 0 + 8v = 9 + -10 8v = 9 + -10 Combine like terms: 9 + -10 = -1 8v = -1 Divide each side by '8'. v = -0.125 Simplifying v = -0.125
| 3.5*2= | | x-19=23 | | 5d+8=53 | | 4x+9-7x=-6 | | 90-x=3/4(180-x)-60 | | 4x+9-7x=-9 | | 0.75=w+2/5 | | (x^2-11)/(2x-1) | | (3/4)x-(7/12)=1 | | 11x-4x=27 | | z/2+1+3/2 | | 3(6x+3)=27 | | 5(2x-4)-(3x+1)=2 | | 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 | | 5+22a=2+10/22 | | 1/4c+2=8 | | 8/4=(6)(0) | | -.2(x+10)-.25(x-4)=x+8 | | 6(X+2)-7=18 | | 0.7t=0.3+0.4t | | 4x-2=9x+1 | | -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= | | -6(-3a-4)= | | -17r=17 | | -5+11x=11x-5 |